Aloe Vera Effectiveness for Perineal Wound Healing for Post Partum Mothers - Dainty Maternity; Renny Dwijayanti; Susilawati Susilawati (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2022)
ABSTRACT: Background: Perineal rupture is the cause of postpartum maternal bleeding. Postpartum hemorrhage is the main cause of 40% of maternal deaths in Indonesia. One way of natural treatment is by giving aloe vera which can speed up the wound healing process. Purpose: This study aims to determine the effectiveness of aloe Vera as a wound medicine on the perineum of postpartum women. Methods: This type of research iwas quantitative research with a quasi-experimental approach. The subjects of this study were mothers who experienced I and II degree perineal rupture in the Karang Anyar Health Center Work Area, South Lampung as many, a sample of 51 respondents. Data obtained from questionnaires. Data analysis used for univariate and bivariate analysis were independent t-test. Results: The data showed that the average score of perineal wound healing due to the use of aloe vera was 4.72, with a standard deviation of 1.815. while the average score of perineal wound healing that did not use aloe vera was 7.35, with a deviation of 2.545. There is a difference in the effectiveness of using aloe vera on perineal wound healing in postpartum mothers at Karang Anyar Health Center, South Lampung with P-value = 0.026.. Conclusion: The use of aloe vera was very effective for healing perineal wounds in postpartum mothers and could be used as an option in accelerating the healing of perineal wounds.